Utilization of manure of buffalo and goats on growth of Kelor plants in Pangururan District Samosir Regency - Ervina Siregar; Nurzainah Ginting; Edhy Mirwandhono; Sayed Umar; Hamdan Wahyuni (Jurnal Peternakan Integratif, 2018)
The need for livestock feed is crucial in Pangururan subdistrict of Samosir Regency. Therefore, it is worthed planting various alternative feed plants such as Kelor (Moringa oleifera). Goat and buffalo feces can be utilized by the community as solid manure. This study aims to utilize the manure density of goat and buffalo againts growth of Kelor (Moringa oleifera). This research was conducted in Pangururan Subdistrict of Samosir Regency of North Sumatera starting from March to May 2018. The research design used in this research was Complete Randomized Design (RAL) with 4 treatments of 5 replications. The treatments consisted of P0 (100% top soil), P1 (50% top soil + 50% Buffalo manure), P2 (50% top Soil + 50% Goat Manure), and P3 (50% top soil + 25% buffalo Manure + 25% Goat Manure). The parameters observed were the effect of treatments on soil pH, leaf width, number of tertier branch. The results showed that 50% top soil + 25% buffalo manure and 25% Goat Manure was better than 100% top soil +50% top soil + 25% Cow Manure + 25% Goat Manure significantly (P <0.05) better than 50% top soil + 50% Cow Manure Buffalow and 50% top soil + 50% Goat Manure to the effect of soil Ph on buffalo and goat manure, leaf width, number of branch children of Moringa oleifera.